Analysis of the Economic Condition of Street Vendors in Jayapura City Post the Covid-19 Pandemic - La Maga; Rachmaeny Indahyani (AIBPM Publisher, 2024)
The analysis of differences in the income of street vendors during the pandemic and after the Covid-19 pandemic was analyzed using the paired sample t-test method using the SPSS 27 for Windows program. Data analysis was carried out in two stages, first as a requirement to perform paired sample t-test analysis. The second is to test the research hypothesis, for the analysis requirements in the form of a data normality test, the data normality test uses the One-Sample Kolmogorov-Smirnov Test. All parametric assumption tests were performed at a significance value of 5%. The results of the analysis in this study show that the total production during the Covid-19 pandemic was 2,876 units/day. Meanwhile, the post-pandemic production amounted to 6,068 units/day. Total income during the Covid-19 pandemic was IDR 122,591,634/month. Meanwhile, the total income after the Covid-19 pandemic was IDR 396,852,124/month. After testing using the SPSS-27 program, it shows that the value of Sig. (2-tailed) = 0.000 ? = 0.05. Then reject the hypothesis H0 and accept the hypothesis H1. Thus, statistically there is a significant difference in the income of street vendors in Yahim Village, Yabansai District, Jayapura City during the pandemic and after the Covid-19 pandemic. This means that street vendors' income has increased after the Covid-19 pandemic